Bardet-Biedl syndrome: a multisystem disorder with rare dermatological manifestations - Ghafoor Ullah; Shabbir, Sidra; Hanniya Marwat; Fahad Faizullah; Maisan Qadir; Maryam Sardar (Journal of the Pakistan Medical Association, 2025)
Bardet-Biedl syndrome (BBS) is a disorder of primary ciliary dysfunction, having a wide range of systemic and dermatological manifestations. We report the case of a nine-year-old patient having multiple erythematous plaques over the dorsal surface of both feet, scalp seborrhea, keratosis pilaris, and polydactyly, associated with night blindness and central obesity. Initial workup corelated well with BBS reporting metabolic syndrome, retinal dystrophy, and gonadal dysfunction. Genetic testing for disease confirmation was not done due to the limited hospital resources. Multidisciplinary symptomatic management was carried out for the patient, along with counselling of the parents regarding possible complications of the disease. This case was reported at the Dermatology Department of Medical Teaching Institute-Hayatabad Medical Complex, Peshawar. Keywords: Bardet-Biedl syndrome, Cone-rod dystrophy, Ciliopathic disorder, Polydactyly, Acanthosis nigricans, Keratosis pilaris.